Hubungan antara Kecepatan dan Kondisi Geometrik Jalan yang Berpotensi Menyebabkan Kecelakaan Lalu Lintas pada Tikungan - Purwanto, Djoko; Kusuma Indriastuti, Amelia; Hari Basuki, Kami (MEDIA KOMUNIKASI TEKNIK SIPIL, 2015)
To date, the traffic accident number on hairpin curve is still quite high. This is exacerbated by speeding driving behaviour of some road users.This research aims to identify the factors that cause traffic accidents and drivers’ behaviour at the curve; to review curve geometric design; and to develop a relationship among speed, curve geometric condition and the accident at the curve. This study simply reviewed three hairpin curves that were prone to be blackspots in Batang. The dominant factors that cause accidents were human error and road condition. The driver’s speeding behaviour was indicated by the speed that was lessen when entering and increase when leaving the curve. There were speed variations among vehicles in research location that could increase the number of accident. The results of the geometric review showed that the radius of all curves evaluated did not meet the standard, i.e. less than the minimum radius. Another result of this study was relationships among speed, geometric condition and accident number, as shown by the following formula: Speed = 0.095 Radius + 42.889, No. of accident = - 0.785 Radius + 0.008 Speed - 284.301, and EAN = 0.028 Speed  - 1108.689.